Losing a Herd Mate: Negative Effects on Milk Yield and Udder Health Indicators in Loose-Housed Dairy Cattle - Barbora Valníčková; Jitka Bartošová; Luděk Bartoš (Animals)
Feral cattle (Bos taurus) live in socially stable herds. Due to farm management practices, intensively managed dairy cows experience frequent regrouping, which can disrupt affiliative bonds and induce social stress. This study examines how changes in herd composition affect milk yield and udder health traits in resident dairy cows exposed to the withdrawal of herd members or the introduction of new individuals. Milk yield, electrical conductivity, and blood presence in milk were measured in 798 cows using precision dairy sensors over 9 years. Milk yield decreased significantly (p < 0.001) one day after the removal of familiar herd members, while introducing cows had no effect. A higher number of cows being withdrawn (up to 10) was associated with reduced milk yield (p < 0.001), elevated milk electrical conductivity (p = 0.01), and an increased prevalence of blood presence in milk (p = 0.01), which can indicate potential udder health issues linked to social stress. Holstein Friesian, primiparous, and first-lactation-stage cows were more affected than Czech Simental and multiparous cows later in lactation. These findings underscore the influence of social stability on dairy cow welfare and productivity, emphasising the need for strategies to mitigate stress when herd changes are necessary.